Routing control method of hot standby BRAS in IP MAN - Huanyi WANG; Guofu XIANG (Dianxin kexue)
With the implementation of“Broadband China”strategy,IP services become more and more diversified,the demand for all kinds of security is also increasing.The key technology of BRAS hot backup and its realization method were introduced,realizing the seamless handover between primary and standby BRAS and effectively controlled the route range in BRAS.The routing was optimized to reduce traffic between interconnect circuits of primary and backup BRAS to improve the utilization efficiency of the circuit.